DEVELOPMENT OF E-LKPD BASED ON PROBLEM BASED LEARNING ON SERVICE ENTERPRISE ACCOUNTING FOR CLASS X AKL IN SMK - Cahyana, Afiqoh; Hakim, Luqman (Universitas Muhammadiyah Surakarta, 2024)
This research and development is motivated by because the LKPD teaching materials used to support accounting learning activities for service enterprise accounting at SMKN 1 Surabaya do not attract students’ interest in learning, are not based on problem based learning, and do not utilize electronic media such as smartphones or laptops. The use of interesting and creative teaching materials by utilizing technology can help understand the material and reduce boredom in learning. This study aims to develop E-LKPD based on problem-based learning, analyze the feasibility of E-LKPD based on problem-based learning, and analyze students' responses of using E-LKPD based on problem based and learning on service enterprise accounting for class X AKL at SMKN 1 Surabaya. Researchers used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research model developed by Branch. The results of this study are E-LKPD based on problem-based learning obtained an assessment from material experts reaching 90% with the category “very feasible”, an assessment from media experts reaching 95% with the category “very feasible”, an assessment from linguists reaching 99% with the category “very feasible”, and student responses after using teaching materials reaching 97% with the criteria “very understanding”. Therefore, E-LKPD is effectively used in the learning process.